Tools for context-aware learning design and mobile delivery - Zervas, P.; Ardila, S.; Fabregat, R.; Sampson, Demetrios (2011)
An important success factor for ubiquitous and mobile learning is the pedagogically meaningful and technically feasible process of learners' contextual information. Thus, in order to achieve personalized and ubiquitous learning, tools for context-aware adaptive learning designs (authoring tools) and context-aware adaptive delivery of learning activities (run-time tools) are needed. In this paper, we target addressing this issue, that is, we describe design requirements for tools that incorporate a context-aware content adaptation mechanism at both the learning design and mobile delivery process. © 2011 IEEE.